Numerical modelling of a coaxial Stirling pulse tube cryocooler with an active displacer for space applications - Rana, H; Abolghasemi, MA; Stone, R; Dadd, M; Bailey, P (Elsevier, 2020)
A numerical model for a coaxial Stirling pulse tube cryocooler with an active displacer has been developed. An active displacer, in place of an inertance tube, has already demonstrated good efficiency in an in-line pulse tube, but incorporating this design into a coaxial configuration permits better access to the cold head. A model of the coaxial cold head was developed to include the radial flow and cooling in this region. The sub-assembly models were validated with flow testing of the physical sub-units of the cryocooler. The performance has been predicted for the cryocooler as a function of: fill pressure, operating frequency, and phase angle between the position of the linear compressor and displacer. The projected difference in performance and efficiency of the coaxial configuration was compared to the in-line design. The coaxial cryocooler numerically simulates 6 W of cooling at 80 K with an input power of 85 W, at a fill pressure of 28 bar, an operating frequency of 60 Hz, and a compressor-displacer phase angle of 41°. Overall, the coaxial cryocooler outperforms the in-line design in terms of cooling power, but not in terms of efficiency.